Weight change across adulthood in relation to the risk of depression - Wang, Tao; Dai, Bingqin; Shi, Huanchen; Li, Huawei; Fan, Kexin; Zhang, Dongfeng; Zhou, Yunping (Frontiers in Psychology, 2023)
Background Studies examining weight change patterns and depression are scarce and report inconsistent findings. This study—aimed to elucidate the association between weight change patterns and the risk of depression in a large, representative sample of US adults. Methods Data from the National Health and Nutrition Examination Survey (NHANES) 2005–2018 was analyzed. Five weight change groups were categorized: stable normal, weight loss, weight gain, maximum overweight, and stable obesity. Depression was ascertained using the validated Patient Health Questionnaire (PHQ-9) and depression was defined as PHQ score ≥ 10. Results A total of 17,556 participants were included. Compared with participants who maintained normal weight, stable obesity participants had increased risks of depression across adulthood from age 25 years to 10 years before the survey (OR = 1.61, 95% CI =1.23 to 2.11), in the 10 years period before the survey (OR = 2.15, 95% CI =1.71 to 2.70), and from age 25 years to survey (OR = 1.88, 95% CI =1.44 to 2.44). Weight gain was associated with an increased risk of depression from age 25 years to 10 years before the survey (OR = 1.71, 95% CI = 1.41 to 2.04), in the 10 years period before the survey (OR = 1.73, 95% CI = 1.35 to 2.21), and for the period from age 25 years to survey (OR = 1.83, 95% CI = 1.49 to 2.24). In the stratified analyses, we found statistically significant interactions with sex. Conclusion Our study suggested that stable obesity and weight gain across adulthood were associated with increased risks of depression.